Pelaksanaan Fardu Kifayah Janazah Analisis Nilai Interkoneksi - Muhammad Shulhi Alhadi Siregar (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2021)
capping should be done as soon as possible. The point is that the mourners immediately pray, try to have at least 100 people, both children and adults, women or men. The place is in the funeral home, so that it is easy to get 100 people. Make an agreement with the village community, every time someone dies, they must join in praying. Benefits of praying 100 people Allah accepts all prayers that pray. It is very easy to deliver the bodies to heaven, only 100 people. Before dying, try to do what is ordered and stay away from everything that is forbidden. The reward for those who pray is given 2 qiroth or 2 mountains of Uhud. If the prayers have been received, why not try 100 people. The more confident you are in slaughtering the animal for alms on the day of your death, the more you eat, the more certain you will go to heaven. Those who pray a little or less than 100 people. If you don't slaughter, it's not good for your child to be unfilial. Sometimes adding to the debt because of slaughtering a buffalo or ox. Sometimes eating at the place of death, which leaves orphans again. It's still worth eating at that place. So that it is forbidden to change the law to eat the property of the orphans, it becomes a sin if you do not eat the property of the orphans.